Gambaran Kondisi Sanitasi Rumah Sakit pada Rumah Sakit Umum Daerah (RSUD) Naibonat Kabupaten Kupang - Yedutun Kase; Agus Setyobudi; Grouse T.S. Oematan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Sanitation is an effort made by humans to create and ensure environmental conditions (especially the physical environment, including soil, water, and air) that meet health requirements. Hospital sanitation is a part of hospital environmental health, aimed at reducing adverse effects such as bacterial contamination and hazardous substances in the hospital environment, which can lead to disease transmission and infection occurrences. This study aims to describe the sanitation conditions of Naibonat Regional General Hospital in Kupang Regency in 2024 using a descriptive quantitative approach, with the research population consisting of all staff members at the hospital. The study results indicate that hospital water health, including drinking water quantity, hygiene and sanitation water quantity, drinking water quality, and hygiene and sanitation water quality, scored 1,400. The health of facilities and buildings, covering visitor toilets, disability toilets, hospital floors, and hospital doors, scored 1,360. Waste management, including domestic solid waste, hazardous and toxic solid waste (B3), and liquid waste, scored 800, while linen management, comprising internal and external linen handling, scored 850. These findings provide an overview of the sanitation conditions at Naibonat Regional General Hospital in Kupang Regency.